Comparison of immediate outcomes between patent ductus arteriosus stenting and modified Blalock-Taussig Thomas shunt in children: a single-center cohort study in Indonesia - Novik Budiwardhana; Indah Kartika Murni; Radityo Prakoso; Pribadi Wiranda Busro; Fildza Intan Rizkia; Muhamad Faza Soelaeman; Yunita Widyastuti (Indonesian Pediatric Society, 2026)
Background Patients with congenital heart diseases (CHD) involving duct-dependence or inadequate pulmonary blood flow often require early palliative interventions to establish a reliable source of pulmonary circulation. Two common palliative procedures in congenital heart surgery are the modified Blalock-Taussig Thomas (mBTT) shunt and patent ductus arteriosus (PDA) stenting. In developing countries like Indonesia, reducing early mortality and morbidity associated with these procedures remains a significant challenge. A better understanding of which procedure is more suitable under specific clinical circumstances is required to improve outcomes. Objective To compare the immediate outcomes between PDA stenting vs. mBTT shunt in pediatric patients with congenital heart disease as duct-dependence or inadequate pulmonary blood flow requiring aortopulmonary connection. Methods This retrospective cohort study was conducted using hospital data collected between January 2020 and December 2023. During the study period, 228 patients underwent mBTT shunt and 94 underwent PDA stenting. After restricting the cohort to infants ≤12 months and excluding cases with incomplete data, 169 patients were eligible for analysis: 86 in the mBTT shunt group and 83 in the PDA stent group. Results The PDA stent group was significantly younger and had lower body weight than the mBTT shunt group (P<0.001). The mBTT shunt group had longer hospital stays (P=0.014) and higher rates of complications, including shunt obstruction (P=0.042), over-shunting (P=0.007), and arrhythmias (P=0.038). Mortality was higher in the PDA stent group (22.9% vs. 15.1%, respectively), but this difference was not statistically significant (P=0.274). Conclusion PDA stenting was associated with better immediate clinical outcomes compared to mBTT shunt, including shorter PICU and hospital stays, lower vasoactive inotropic score (VIS), reduced over-shunting, and fewer complications. Although mortality was higher in the PDA stent group, the difference was not statistically significant.